2020
DOI: 10.1097/jom.0000000000002102
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake Among Members of a Volunteer Fire Department Compared With US Daily Dietary Recommendations

Abstract: Objective: To characterize the diet of volunteer firefighters compared with the United States recommended dietary intake. Methods: A survey was administered to members of volunteer fire department which collected information on demographics, behavioral risks, fire service history, and dietary intake using the Dietary Screener Questionnaire. Dietary intake was compared with US recommendations; associations between dietary intake and years of firefighting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Epidemiological studies observed that firefighters have a high consumption of red meat and fast food [74,75]. Similarly, fat, cholesterol, protein, sugar, and sodium were overconsumed, whereas fruits, vegetables, grains, and dietary fibers were below recommended levels [61,76]. Evidence from surveys shows that the Mediterranean diet could be the most appealing healthy diet option accepted by many firefighters [58], and is consistent with revised US government dietary guidelines [58].…”
Section: Nutritionmentioning
confidence: 77%
“…Epidemiological studies observed that firefighters have a high consumption of red meat and fast food [74,75]. Similarly, fat, cholesterol, protein, sugar, and sodium were overconsumed, whereas fruits, vegetables, grains, and dietary fibers were below recommended levels [61,76]. Evidence from surveys shows that the Mediterranean diet could be the most appealing healthy diet option accepted by many firefighters [58], and is consistent with revised US government dietary guidelines [58].…”
Section: Nutritionmentioning
confidence: 77%
“…Evidence from the literature indicates that SFFs have a high consumption of red meat and fast food contributing to the insufficiency of consumed calories relative to the energy expenditure needed for firefighting [ 6 , 23 ]. SFFs, during their shift, have been observed to over consume fat, cholesterol, protein, sugar, and sodium, and under consume fruits, vegetables, whole grains, and dietary fiber than is recommended [ 24 , 31 ]. More recent studies also indicated that SFFs consume inadequate amounts of linolenic fatty acids, fiber, potassium, magnesium, zinc, and vitamins D, E, and K with vitamin D, magnesium, and potassium having the greatest shortcomings [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The survey was conducted online using REDCap, a secure survey management system 14 . The survey questions were adapted from the Fire Fighter Cancer Cohort Study (FFCCS) enrollment survey, 15 with modifications specific to volunteer firefighters 16–18 . The study was approved by the University of Arizona Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%